Selection of half-sib families of creole melon (Cucumis melo L.) on the Ecuadorian coast - Espinosa, Francisco; Vallejo, Franco Alirio; Rizzo, Lauden (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
The creole melon cantaloupe is a horticultural species, whose fruits are used for human nutrition. However, no research has been reported on their genetic variability for starting breeding processes. The objective of this study was to take advantage of the variability of creole melons for genetic improvement. 20 creole melon half-sib families were selected and evaluated for production characteristics and fruit quality in order to obtain improved populations. The study was carried out in Palenque canton, Ecuador. Seeds from 20 half-sib families were used, arranged in a randomized complete block design with three replications. The differences between the families were significant for all the studied characteristics. Family 93 presented higher averages for fruit weight, fruit diameter and production (per hectare), and family 196 did so for soluble solids. The phenotypic correlations were positive and significant between the fruit weight and fruit diameter, fruit length, pulp thickness, fruit cavity, soluble solids and production. The coefficients of genetic variation, in general, were lower than the coefficients of environmental variation. The estimates of heritability broadly had a moderate magnitude (30-60%) for the 10 evaluated characteristics, and the magnitude of the expected genetic progress was low (<10%) for the fruit weight, production, and soluble solids, so the selection for high production should focus on fruit weight and soluble solids.